Musculoskeletal Disorders (MSDs) Risk Level at Cleaning Service Workers in Integrated Facility Services - Kusumaningtiar, Devi Angeliana; Favianto, M. Rafi Favianto; Izzatu Millah, Izzatu Millah; Cut Alia Keumala Muda (YCAB Publisher, 2025)
Background: Cleaning service workers are among occupational groups with a high potential for ergonomic risks due to the predominantly manual nature of their work activities. A preliminary study utilizing the Nordic Body Map (NBM) questionnaire revealed that all cleaning service workers surveyed (100%) reported experiencing musculoskeletal disorder (MSD) symptoms. Objective: To analyze the risk level of Musculoskeletal Disorders (MSDs) among cleaning service workers at Integrated Facility Services. Methods: This study employed a descriptive-analytic approach with a cross-sectional design. The research was conducted at Integrated Facility Services in South Tangerang. Primary data were collected using the Nordic Body Map (NBM) questionnaire and the Rapid Entire Body Assessment (REBA) tool. Univariate data analysis was performed using computerized statistical applications. Results: Among cleaning service workers at Integrated Facility Services, 26 individuals (55.3%) reported a low level of MSD complaints, 19 individuals (40.4%) reported a moderate level, and 2 individuals (4.3%) reported a high level of complaints. In terms of posture-based risk assessment using the REBA method, 3 workers were categorized as having a low MSD risk, 4 workers as moderate risk, and 2 workers as high risk. Conclusion: Dusting and toilet cleaning were identified as tasks with the highest ergonomic risk, primarily due to awkward working postures. These findings indicate the need for immediate corrective interventions and ergonomic improvements to reduce the risk of MSDs among cleaning service workers. Keywords: Musculoskeletal Disorders (MSDs); posture; occupational ergonomics; cleaning service workers; Rapid Entire Body Assessment (REBA)